Zirconosilicates in the kakortokites of the Ilímaussaq complex, South Greenland: Implications for fluid evolution and high-field-strength and rare-earth element mineralization in agpaitic systems. (1st February 2016) - Borst, A. M.; Friis, H.; Andersen, T.; Nielsen, T. F. D.; Waight, T. E.; Smit, M. A.
The layered agpaitic nepheline syenites (kakortokites) of the Ilímaussaq complex, South Greenland, host voluminous accumulations of eudialyte-group minerals (EGM). These complex Na-Ca-zirconosilicates contain economically attractive levels of Zr, Nb and rare-earth elements (REE), but have commonly undergone extensive autometasomatic/hydrothermal alteration to a variety of secondary mineral assemblages. Three EGM alteration assemblages are recognized, characterized by the secondary zirconosilicates catapleiite, zircon and gittinsite. Theoretical petrogenetic grid models are constructed to assess mineral stabilities in terms of component activities in the late-stage melts and fluids. Widespread alteration of EGM to catapleiite records an overall increase in water activity, and reflects interaction of EGM with late-magmatic Na-, Cl- and F-rich aqueous fluids at the final stages of kakortokite crystallization. Localized alteration of EGM and catapleiite to the rare Ca-Zr silicate gittinsite, previously unidentified at Ilímaussaq, requires an increase in CaO activity and suggests post-magmatic interaction with Ca-Sr bearing aqueous fluids. The pseudomorphic replacement of EGM in the kakortokites was not found to be associated with significant remobilization of the primary Zr, Nb and REE mineralization, regardless of the high concentrations of potential transporting ligands such as F and Cl. We infer that the immobile behaviour essentially reflects the neutral to basic character of the late-magmatic fluids, in which REE-F compounds are insoluble and remobilization of REE as Cl complexes is inhibited by precipitation of nacareniobsite-(Ce) and various Ca-REE silicates. A subsequent decrease in F– activity would furthermore restrict the mobility of Zr as hydroxyl-fluoride complexes, and promote precipitation of the secondary zirconosilicates within the confines of the replaced EGM domains.